2012
DOI: 10.1039/c2pp25184a
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and photocatalytic selectivity of SrWO4:Ln3+ (Eu3+, Tb3+, Sm3+ and Dy3+) prepared by a supersonic microwave co-assistance method

Abstract: The chemical effects of high intensity ultrasound and microwave irradiation on lanthanide (Eu(3+), Tb(3+), Sm(3+) and Dy(3+)) activated SrWO(4) phosphors were extensively studied. Four classes of characteristic optically active materials (red, green, orange-red and blue-yellow) with striking luminescence were facilely prepared under very low temperature (70 °C) in 45 min. Particularly, Sm(3+), Dy(3+) and Eu(3+) doped strontium tungstates were visible-light driven emissive. The photocatalytic properties of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…A similar CT band was observed in the 146 Dy 3+ doped LaBWO 6 in our experiments(Fig. 5).which was attributed to an electric-dipole transition[8].Commission International de I ' Eclairage (CIE) 1931 x-y chroma-155 ticity diagram of La 0.94 Sm 0.06 BWO 6 phosphors were presented in…”
supporting
confidence: 77%
“…A similar CT band was observed in the 146 Dy 3+ doped LaBWO 6 in our experiments(Fig. 5).which was attributed to an electric-dipole transition[8].Commission International de I ' Eclairage (CIE) 1931 x-y chroma-155 ticity diagram of La 0.94 Sm 0.06 BWO 6 phosphors were presented in…”
supporting
confidence: 77%
“…SrWO [17,18,27]. Due to their featured crystal structure, rare earth doped SrWO 4 materials have been proposed as a potential candidate for various electro-optical and scintillating device applications [18][19][20][21][22][23][24][25][26][27]. From earlier reports, it was found that the doping of Nd 3?…”
Section: Introductionmentioning
confidence: 98%
“…compounds synthesized by hydrothermal method exhibits interesting and promising green phosphor for fluorescent lamp applications [22]. Zheng et al [23] reported that the rare earth doped SrWO 4 compounds synthesized by supersonic microwave co-assistance method showing enhanced photocatalytic behaviour. Recently, Xu et al [24] reported that the Eu 3?…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations